Improving Chemical Literacy Skills: Integrated Socio-Scientific Issues Content in Augmented Reality Mobile - Sulistina, Oktavia; Samudra Mutiara Hasanah, (International Journal of Interactive Mobile Technologies (iJIM), 2024)
This research aims to develop socio-scientific issues (SSI) content on chemical bonding material and is used to measure students’ chemical literacy abilities. Currently, the chemistry literacy level of high school students is still relatively low, so a process of reconstructing the structure of chemistry learning content that is linked to real-life contexts is needed. One way to develop this material is to include SSI content in learning. SSI content includes articles containing reading and images as augmented reality (AR) markers, which will later be linked to AR technology on smartphones so that students’ chemical literacy can increase. This study uses the R&D method with the ADDIE design. Research instruments used include material validation, media validation, student response tests, and chemical literacy pre- and post-test instruments. The results of SSI content validation have been declared feasible for use in learning (91.58% material validation; 91.33% media validation; 91.57% student responses). The implementation results show that SSI content has a significantly positive effect on students’ level of chemical literacy skills. Student responses also show that the SSI content developed is easy to understand and motivates students to learn.